Evaluasi pasca panen, cacat mutu dan atribut kimia (kafein, asam klorogenat) kopi robusta Lampung Barat (studi kasus gapoktan di Lampung Barat)[Identification of post-harvest, quality defects, and chemical characteristics (caffeine, chlorogenic acids) of West Lampung robusta coffee beans (Case Study of Gapoktan in West Lampung] - Analianasari Analianasari; Eko Kenali Win; Dayang Berliana; Meinilwita Yulia; Shintawati Shintawati (Jurnal Teknologi & Industri Hasil Pertanian, 2022)
Post-harvest Robusta coffee conducted by local farmers in West Lampung consisted of two post-harvest processes: dry processing (natural, honey) and wet processing (full wash). The study aimed to identify the post-harvest process stages, the value of quality defects and to characterize the chemical composition (chlorogenic acid, caffeine) of coffee beans from different post-harvest processes produced by Gapoktan Triguna Tribudi Syukur, West Lampung. The research used survey and interview methods equipped with laboratory analysis. The research sample was determined by purposive sampling, a coffee producer (Gapoktan Triguna) who have been fostering coffee in West Lampung for 35 years. Coffee quality analysis refered to SNI 01-2907-2020. The results showed that the post-harvest process carried out by Gapoktan Triguna on honey, natural and full wash processing produced premium quality of of coffee beans (1-2 quality) with the highest number of quality defects produced were broken beans. The roasting process with semi-mechanical and mechanical machines with natural processing produced high chlorogenic acid content (>3%) and the caffeine content according to the SNI caffeine content (2%). Keywords: caffeine, chlorogenic acid, defects, post-harvest, Robusta